2016
DOI: 10.1002/eco.1719
|View full text |Cite
|
Sign up to set email alerts
|

Biocrusts positively affect the soil water balance in semiarid ecosystems

Abstract: Biocrusts play crucial roles in hydrological processes by controlling soil water availability and regulating water redistribution from source to sink areas. Most studies have examined the influence of biocrusts on isolated components of the soil water balance, but few have addressed this matter from an integrated point of view, involving their influence on all components together. Such integration is crucial to elucidate the overall effects of biocrusts on the soil water balance. The aim of this study was to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
123
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(144 citation statements)
references
References 68 publications
3
123
1
3
Order By: Relevance
“…To the best of our knowledge, only one study explores the effects of both grazing and aridity on biocrusts (Mallen-Cooper et al, 2018). Considered to be the 'living skin' of soils in drylands (Bowker et al, 2018), biocrusts play key ecological roles: they stabilize soils, thus reducing rates of wind erosion and dust particle production , regulate soil surface temperature (Couradeau et al, 2016), drive soil C (Grote et al, 2010), N (Torres-Cruz et al, 2018), and P (Baumann et al, 2018) cycles, control runoff-infiltration dynamics (Chamizo et al, 2016), and modulate the establishment of plants (Ferrenberg et al, 2018). Considered to be the 'living skin' of soils in drylands (Bowker et al, 2018), biocrusts play key ecological roles: they stabilize soils, thus reducing rates of wind erosion and dust particle production , regulate soil surface temperature (Couradeau et al, 2016), drive soil C (Grote et al, 2010), N (Torres-Cruz et al, 2018), and P (Baumann et al, 2018) cycles, control runoff-infiltration dynamics (Chamizo et al, 2016), and modulate the establishment of plants (Ferrenberg et al, 2018).…”
mentioning
confidence: 99%
“…To the best of our knowledge, only one study explores the effects of both grazing and aridity on biocrusts (Mallen-Cooper et al, 2018). Considered to be the 'living skin' of soils in drylands (Bowker et al, 2018), biocrusts play key ecological roles: they stabilize soils, thus reducing rates of wind erosion and dust particle production , regulate soil surface temperature (Couradeau et al, 2016), drive soil C (Grote et al, 2010), N (Torres-Cruz et al, 2018), and P (Baumann et al, 2018) cycles, control runoff-infiltration dynamics (Chamizo et al, 2016), and modulate the establishment of plants (Ferrenberg et al, 2018). Considered to be the 'living skin' of soils in drylands (Bowker et al, 2018), biocrusts play key ecological roles: they stabilize soils, thus reducing rates of wind erosion and dust particle production , regulate soil surface temperature (Couradeau et al, 2016), drive soil C (Grote et al, 2010), N (Torres-Cruz et al, 2018), and P (Baumann et al, 2018) cycles, control runoff-infiltration dynamics (Chamizo et al, 2016), and modulate the establishment of plants (Ferrenberg et al, 2018).…”
mentioning
confidence: 99%
“…Biocrusts are complex, topsoil microbial assemblages that develop on the primary production of soil cyanobacteria, microalgae (sometimes in algal symbioses), or mosses and that support a large diversity of heterotrophic bacteria (9), archaea (10), and fungi (11). Considered to be a "mantle of fertility" in arid lands (12), biocrusts provide essential goods and services; they stabilize soils and thus reduce rates of wind erosion and dust particle production (13), can influence soil temperature (14,15), contribute significantly to soil C and N inputs into the ecosystem (16), increase the lixiviation of micronutrients (17), control soil hydrological dynamics (18), and are thought to provide good conditions for plant germination and establishment (19).…”
mentioning
confidence: 99%
“…Cyanobacteria have a positive effect upon water retention due to the production of polysaccharide exudates determining hydrophilic soil properties (Belnap, ). Heterogeneous effects have been reported for lichen‐dominated BSCs (Belnap, ; Chamizo et al., ). We found that soil moisture is mainly related to the presence of crustose and squamulose lichens with an umbiculus or rhizohyphae as anchoring organs (Tables and ), in clear contraposition to the conception that lichens with these morphologies seal soil pores (Belnap, ; Chamizo et al., ; Rodríguez‐Caballero et al., ).…”
Section: Discussionmentioning
confidence: 98%